Análisis de la gestión de riesgo de crédito en el sector financiero del Banco Guayaquil - Martínez Bajaña, Miguel Angel (2024)
Currently, the financial system is affected by numerous factors impacting credit risk management, including the political situation in our country, as well as social and economic conditions. Through the analysis conducted, it is evident how Banco Guayaquil manages to prevent the materialization of its risks, particularly credit risk. As a large institution within the country, it requires greater controls and countermeasures to adequately manage its risks. However, this does not mean it is exempt from the possibility of its loan portfolio becoming overdue or from its granted loans being adequately liquidated. This study allowed for an appropriate analysis of the bank's policies and controls to mitigate credit risk as much as possible.